Efficacy and safety of LABA/LAMA fixed-dose combinations approved in the US for the management of COPD. (2nd July 2016) - Banerji, Donald; Mahler, Donald A.; Hanania, Nicola A.
ABSTRACT: Introduction : Long-acting β2 -agonists [LABAs] and long-acting muscarinic antagonists [LAMAs]) are primary therapies for chronic obstructive pulmonary disease (COPD). Despite improvements in lung function and patient-reported outcomes (PROs) with these therapies, there is room to optimize outcomes further. Combined use of LABAs and LAMAs is recommended when symptoms are not improved with a single agent, and LABA/LAMA fixed-dose combinations (FDCs) are at the forefront of drug development in COPD. Areas covered : This review focusses on the three LABA/LAMA FDCs (indacaterol/glycopyrrolate 1 [IND/GLY] 27.5/15.6 µg twice daily, umeclidinium/vilanterol [UMEC/VI] 62.5/25 µg once daily and tiotropium/olodaterol [Tio/Olo] 5/5 µg once daily approved in the US. Phase III clinical trials have shown benefits in lung function, dyspnea and health status with FDCs of IND/GLY, UMEC/VI and Tio/Olo versus placebo and monotherapies. Expert commentary : Data from recent studies of three LABA/LAMA combinations, reviewed here, indicate that dual bronchodilation may be beneficial above and beyond both the monotherapies and LABA/ICS combinations, in providing improvements in lung function and PROs for patients with COPD, which may encourage a shift away from the use of ICS in COPD management, in particular for non-exacerbating patients.